Parents’ online coaching in the early intervention home program for toddlers with autism spectrum disorder during the COVID- 19 pandemic: Manual development and feasibility study - Png, JieYi; Wan Yunus, Farahiyah; Kadar, Masne; Yang, Wai Wai; Ahmad Rusli, Yasmin; Abdul Khaiyom, Jamilah Hanum (Public Library of Science, 2024)
Early intervention improves the developmental progress among toddlers with ASD. Family involvement enhances the intervention outcome. This study aimed to develop and test the feasibility of an early intervention home program manual for toddlers with ASD. Method: This study involved three phases: (I) formulation of manual concept and content design (II) manual development through focus group discussion (n = 10) and content validation by experts (n = 9); (III) cognitive interview (n = 6) and feasibility study (n = 8). Result: Content Validity Index (I-CVI) for the developed manual ranged from .78–1.0, S-CVI/Ave .96, and SCVI/ UA .79. Cognitive interview among six parents reported that the manual was easy to understand. The feasibility study reported all eight parents benefitted from coaching sessions. Approximately 87.5% of the respondents found the program benefited their children and could easily implement the activities in their daily routines. Approximately 75% of respondents reported having greater confidence in managing their child’s behaviors at home. Parent coaching using the developed home program is feasible and accepted by parents of a toddler with ASD. Further study should be developed to explore the effectiveness of parent coaching using the manual.